Analysis of static balance performance and dynamic postural priority according to playing position in elite soccer players - Jadczak, l.; Grygorowicz, M.; Wieczorek, A.; Sliwowski, R. (Gait and Posture, 2019)
Backgrounds: Balance performance and postural priority are important components of motor skill development. No published reports have investigated the differences in static balance abilities and postural priority among professional soccer players according to field position. Research question: We hypothesized that static balance as well as dynamic postural priority is in uenced by playing position in professional soccer players. Methods: The study covered a group of 101 elite professional soccer players who were divided into six subgroups according to playing positions: goalkeepers (G) (n = 10), central defenders (CD) (n = 15), external defenders (ED) (n = 15), central midfielders (CM) (n = 23), external midfielders (EM) (n = 15) and forwards (F) (n = 23). All participants completed the Delos Postural System Test using the standard protocol. The tests were performed unilaterally on non-dominant (NL) and dominant leg (DL) under static conditions (with open and closed eyes) standing on a stable platform and under dynamic conditions on an unstable base. Results: In the static test with open eyes (ST OE) there were no statistically significant differences between the legs and positions. In the static test with closed eyes (ST CE), the differences are statistically significant only between positions. Players on the CM position have significantly higher differences than G. In the dynamic postural priority test (DPPT) there is a difference between positions and legs. In fact, the statistically higher differentiation refers to players in the CM position relative to ED, CD, EM and F. We noticed a significantly greater difference in the NL compared to the DL. Significance: Static balance performance and postural priority varied with playing position in elite soccer players. Midfield players have better postural priority than players in other positions. Professional soccer players present greater balance postural priority on the non-dominant leg.